SOCIAL MEDIA MARKETING STRATEGY TO INCREASE PURCHASE INTENTION THROUGH BRAND TRUST AND BRAND IMAGE IN LOCAL COFFEE SHOPS ON JAVA ISLAND - Septiana Nurul Kharimah; Eka Sudarmaji (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study examines the effect of Social Media Marketing on Purchase Intention toward local coffee shops in Java Island, with Brand Trust and Brand Image as mediating variables. A quantitative method was used, which involved surveying 376 individuals who actively use social media and have come into contact with promotional content from local coffee shops. Purposive sampling was used, and the data were analyzed through Partial Least Squares–Structural Equation Modeling (PLS-SEM) using SmartPLS 3.2. The findings indicate that Social Media Marketing has a positive and significant effect on Purchase Intention, and also significantly influences Brand Trust and Brand Image. Furthermore, Brand Trust and Brand Image significantly affect Purchase Intention and mediate the relationship between Social Media Marketing and Purchase Intention. These results suggest that effective social media strategies should focus on strengthening brand trust and brand image to enhance consumers’ purchase intention in the increasingly competitive local coffee shop industry. Keywords: Social Media Marketing; Brand Trust; Brand Image; Purchase Intention; Local Coffee Shops